1975
DOI: 10.1113/jphysiol.1975.sp011132
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of fatty acids across the rabbit placenta.

Abstract: SUMMARY1. Transfer of fatty acids across the placenta was studied in anaesthetized rabbits at 28-days gestation by measuring umbilical venous-arterial differences, by injection of labelled palmitate into the mother and observing its appearance in the foetus, by injection of labelled palmitate into the foetus and measuring its appearance in the mother and the foetal clearance rate.2. The release of fatty acids and glycerol by foetal adipose tissues was investigated in vitro by measuring the effect of addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 15 publications
6
71
0
Order By: Relevance
“…Important differences of FFA transfer to the foetus have been demonstrated between species in relation to their placentation. Maternal FFA are readily transferred in several species like rabbits [11,12,24,56] or guinea pigs [57,58], although in sheep the placenta displays poor permeability to this substrate [13]. This latter observation can be extended to the pig since after meal ingestion the maternal plasma FFA drop and it is not accompanied by a studied previously.…”
Section: Resultsmentioning
confidence: 99%
“…Important differences of FFA transfer to the foetus have been demonstrated between species in relation to their placentation. Maternal FFA are readily transferred in several species like rabbits [11,12,24,56] or guinea pigs [57,58], although in sheep the placenta displays poor permeability to this substrate [13]. This latter observation can be extended to the pig since after meal ingestion the maternal plasma FFA drop and it is not accompanied by a studied previously.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements on umbilical blood samples from sheep did not show a net flux in either direction (James, Meschia & Battaglia, 1971). In rabbits and man the umbilical venous-arterial difference varied directly with the maternal FFA blood concentrations (Elphick et al 1975;Elphick et al 1976;Aabata, Wolf & Lausmann, 1968). This would suggest that one factor determining the transfer of fatty acids from the mother to the foetus is the concentration on the maternal side of the placenta.…”
Section: Introductionmentioning
confidence: 90%
“…Infusion of labelled palmitate into foetal rabbits led to its early appearance in the free fatty acid compartment of maternal blood (Elphick, Hudson & Hull, 1975). Thus, fatty acids can be transferred across the placenta in both directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No anabolism has been observed in pregnant rabbits (Lebas, 1975 (Elphick et al, 1975 ;Elphick and Hull, 1977a,b ;Hudson and Hull, 1977 ;Stammers et al, 1983 Robinson and Williamson, 1980). The only data available have shown that blood ketone bodies remain very low throughout pregnancy in rabbits (Gilbert et al, 1984).…”
Section: Introductionmentioning
confidence: 99%